Level of Psychological Hardiness among the elderly in the city of Baniyas in the Light of Some Variables - محمد, سهيلة (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
The purpose of this study was to determine the level of Psychological Hardiness among the elderly in the city of Baniyas, as well as the differences in their Psychological Hardiness according to the variables: age, type of employment, and social level. The sample of the study consisted of (102) elderly in the city of Baniyas To achieve the aim of the study, the researcher used the descriptive research methodology, and the measure of Psychological Hardiness which consists of (42) items. Prepared by researcher: Hijaz, Abu Ghali,(2008), after it was judged and modified to fit the current study. The study showed the following results: - the level of Psychological Hardiness was high. - And the results did not show statistical significant differences in Psychological Hardiness among the sample members according to the variables, age, type of employment, economic level and social level.